Nilai-Nilai Agama Islam sebagai Budaya Sekolah untuk Membangun Peserta Didik yang Berkarakter Religius - Putri Maulida Sabila; Bachtiar Siregar; Hardianto Hardianto (Departement of Mathematics Education, 2024)
School culture plays a crucial role in shaping the character of students, serving as the values and norms guiding their activities. It fosters motivation for learning, collaboration, and the enhancement of positive attitudes in school interactions. The implementation of Islamic religious values within the context of school culture significantly impacts the formation of students' character. This study employs a literature review method, a process involving data collection from various sources such as books, writings, lecture notes, and other relevant sources related to the research object. The implementation of Islamic religious values as part of school culture plays a central role in shaping students' religious character. Islamic school culture, including activities like reciting Yasin every morning, performing congregational prayers, commemorating Islamic holidays, and talent showcase events, contributes to the development of students' religious character. To instill religious character in students, creative breakthroughs are needed in developing a school culture that is Islamic in nature.